Editorial Volume 6 Issue 1 - Ciorstan J. Smark (Australasian Accounting, Business and Finance Journal, 2012)
Welcome to the first issue of AABFJ for 2012. This issue is weighted towards finance and economics with a diverse range of geographical regions represented in this issue’s offerings. Papers in this issue present studies from Indonesia, Italy, Portugal, Australia, Canada, the UK and the US. A variety of ontological approaches are also present, from social constructionist to the assumed realist approaches of the economics and finance articles.
Keywords: Editorial; AABFJ